(3GdedNU GdcGaj aj Ydei GdeYGfi hGdHjGfs - (3YHO GddWja Hf Ydis ((3CMeO Hf jhSa s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje GdMeO ddg Ydi JhGdi BdGFg hJhGJQ fYeGFg hHYO agPG edNU JdNjU GdeaJGM ROJ ajg ef RhGFO GdaQGFO eG jRjO eRjI GdadGM s
(3BNQgG (B:s
(3cbhdge HYO MeO Gddg JYGdi CeG HYO hgh aUd GdNWGH hYfO GdEfJbGd ef MOjK Edi BNQ gPG Ch gPG HGH Ch hCjVkG hCMSfg eG CPf Ci CTYQ HGdEfJgGA s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdHdGZIs